In California, Voluntary Mass Prenatal Screening - Steinbrook, Robert (The Hastings Center report, 1986)
A statewide program in California to detect neural tube and other birth defects may revive enthusiasm for mass prenatal screening. Participation in the program is voluntary, but all expectant mothers are asked to sign a statement of “informed consent/refusal.” So far California's program seems to be working well, but questions for the future include the level of participation, the possibility that normal fetuses will be aborted, the kinds of information given to women, and the elusive nature of free choice.